Social Media Networking and Knowledge Sharing in Increasing Innovation and MSME’s Growth: Based on the Theory of Communication Visibility - Lyna Latifah; Nurdian Susilowati; Muhammad Noor Ardiansah; Tusyanah Tusyanah; Muhammad Syukri Abdullah (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2022)
The purpose of this study is to examine the direct effect of social media networking, knowledge sharing, and innovation on MSME's growth. This study also examines the role of knowledge sharing and innovation in mediating the influence of social media networking on the MSME’s growth. This research is survey research. Respondents are MSMEs from young entrepreneurs assisted by universities. Respondents who participated in this study were 467 people, but only 421 could be used. Data analysis techniques in this study using PLS-SEM. The results show that social media networking, knowledge sharing, and innovation affect MSME's growth. Knowledge sharing and innovation play a part in mediating the influence of social media networking on MSME’s growth. This study examines the role of knowledge sharing and innovation in mediating social media networking on MSME’s growth.